REVIEW OF CFD SIMULATION OF OXY-COAL COMBUSTION FOR ELETRICAL POWER GENERATION: OPPORTUNITIES AND CHALLENGES - Nascimento, F. S.; Nascimento, M. A. R.; Coronado, C. J. R.; Rodrigues, L. O.; Carvalho Jr, J. A.; Dias, F. L G. (Revista de Engenharia Térmica, 2016)
The oxy-combustion has generated significant interested for reduction of CO2 emission when the fossil fuel is coal, due to simplification on the separation process of CO2 from the flue gas, it can be more easily stored in reservoir. The CFD numerical simulation techniques in oxy-coal combustion has the potential to contribute to designers in cost savings and reduced computational time; Furthermore, such techniques also provide a robust tool for better understanding and description of the aerothermodynamics processes involved, as well as, aiding the design of most efficient furnaces. However, to obtain representative results of the physical phenomena, the numerical models employed by CFD needs to be suitable for oxy-coal combustion. So, the aim of the paper is to carry out a review of the recent models that are being used for turbulence, combustion and pollutant emissions. Moreover, it is shown a comparison of different results obtained in the numerical simulation of oxy-coal combustion among new models, existing models and experiments. The analysis of the models and experiments shows that the challenges that are still being faced to obtain better accuracy of numerical simulation results. Improvements in the models for oxy-coal combustion can be seen like potential opportunities to investigate and optimize the process that occur in the combustion.